(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article delves into the realm of oral hygiene, exploring the importance of maintaining optimal oral health and the various practices that contribute to it. Through a literature review, we examine existing research on oral hygiene, discuss effective methods, present key findings, and offer conclusions and suggestions for improving oral care practices.